Evaluation of anti-inflammatory activity of methanolic extract of leaves of Bougainvillea spectabilis in experimental animal models - Mandal, Gautam (Pharmacognosy Res, 2015)
BACKGROUND: Bougainvillea spectabilis (BS) (family Nyctaginaceae) is said to possess hypoglycemic and anti-inflammatory activities in experimental animals. We had set forward to examine the potential anti-inflammatory activities of BS in experimental models of inflammation. MATERIALS AND METHODS: Fresh dried leaves from the flowering plant of BS were collected from the local area during the flowering season and air dried (215.00 g). Methanol was extracted, and the solvent was removed on a rotary evaporator under reduced pressure. The extract was freeze-dried (lyophilized) and the yield was 8 g. This was used as an emulsion prepared in propylene glycol and orally administered (20 and 50 mg/kg). Acute anti-inflammatory activity of BS was evaluated using carrageenan and dextran whereas chronic anti-inflammatory (immunoregulatory) activity was evaluated by Freund's adjuvant-induced arthritis model. RESULTS: BS (20 mg/kg and 50 mg/kg) had shown significant anti-inflammatory effects 20.6% and 67.6%, respectively, on carrageenan-induced acute inflammatory models. In dextran-induced edema, the effect was 30% and 66%, respectively. The standard drug indomethacin (87.3% and 91.5%, respectively) showed better inhibitory response in both models. In arthritic model 50 mg/kg of BS showed significant chronic anti-inflammatory effect (38.46%) in comparison to the standard drug dexamethasone (84.6%). CONCLUSION: Our data indicate that the methanol extract of BS (50 mg/kg) leaves has significant anti-inflammatory and immunoregulatory activity. Further studies involving isolation of active principles will help to pinpoint the mechanisms contributing to the observed activities of BS.